Changes in the collagen fibers arrangement during development of the periodontal ligament in the rat incisor. - Marcelo R. Marques; Messias Franca Macedo; Marco A.D. Silva; Silvana P. Barros (Universidade Estadual de Campinas, 2015)
The aim of this work was to describe the development of the periodontal ligament and the distribution of collagen fibers in lower rats incisors, through picrosirius polarization method. It was observed that transgingival eruption takes place between the days 10-13 with thin collagen fibrils from periodontal ligament more organized in the tooth related region, showing greenish birefringence. Functional occlusion occurred starting from the 16th day of life together with the maturation of ligament fibers that showed either red or yellow intense birefringence. Our findings indicate that the degrees of molecular organization and alignment of collagen fibers in the alveolar bone and tooth-related areas of the ligament are higher than those in the intermediate area and tend to increase near a more incisal region. It is also suggested that the collagen fibers in the intermediate periodontal ligament area remain immature along the long axis of the incisor even after the functional occlusion period is reached.